Watt-level high-stability all-solid-state passively Q-switched laser based on germanene nanosheets - Xu, Baohao; Tang, Wenjing; Sun, Wanggen; Wang, Jing; Jiang, Kai; Hu, Xinyu; Xia, Wei (Frontiers in Physics, 2022)
Excellent Q-switching operations modulated by new two-dimensional (2D) saturable absorber (SA) materials with stable performance is a hot topic in all-solid-state pulsed laser research. In this work, the watt-level high-stability passive Q-switching operation in a solid-state Nd:YVO4 laser utilizing the 2D germanene nanosheets as SA was first realized. The nonlinear optical properties of the germanene nanosheets (Ge-Ns) were characterized by experimental means. The stable Q-switched pulse sequence was acquired with a 60.6 ns narrowest pulse width and a 528.6 kHz maximal repetition rate. The average output power of 0.965 W and the corresponding pulse peak power of 30.12 W are obtained under the pump power of 7 W. The findings of the experiments demonstrate that germanene material has remarkable nonlinear optical properties and can be used as an excellent saturable absorber in the field of optical pulse modulation.